Cultural adaptation of the Michigan Hand Outcomes Questionnaire in patients with Carpal Tunnel Syndrome: A Turkish version study - Ilker Ilhanli; Dilek Durmus; Gulhan Orekici (Chronic Diseases and Translational Medicine, 2015)
Objective: Cultural adaptations of the questionnaires are important for easy use. We aimed to assess the reliability and validity of the Turkish Version of the Michigan Hand Outcomes Questionnaire in patients with Carpal Tunnel Syndrome. Methods: To assess test-retest reliability, the Turkish âMichigan Hand Outcomes Questionnaireâ and âDisabilities of Arm, Shoulder and Handâ questionnaires were answered by patients and controls and were repeated a week later. For testing internal consistency, the Cronbach's alpha test was used. For testing validity, correlations between the subscales of the âMichigan Hand Outcomes Questionnaireâ and âDisabilities of Arm, Shoulder and Handâ questionnaire were measured in patient groups. One hundred patients with idiopathic Carpal Tunnel Syndrome and 50 healthy participants were included in the study. Results: In test-retest reliability, intraclass correlations of the subscales of the âMichigan Hand Outcomes Questionnaireâ were high. Cronbach's alphas were found to be high in all subscales. There was no significant correlation between asthetics and pain scales. We found significant differences between patients and controls regarding all subscales of the âMichigan Hand Outcomes Questionnaireâ. Correlations between subscales of the âMichigan Hand Outcomes Questionnaireâ and âDisabilities of Arm, Shoulder and Handâ questionnaire were significant. We found no difference between one-hand effected and two-hand effected patients, in terms of the âMichigan Hand Outcomes Questionnaireâ, âDisabilities of Arm, Shoulder and Handâ questionnaire Function/Symptom and Work average scores. Conclusion: This study showed that the Turkish version of the âMichigan Hand Outcomes Questionnaireâ is reliable and valid and can be used in Turkish patients with Carpal Tunnel Syndrome because it is comprehensible and practicable. Keywords: Questionnaire design, Carpal tunnel, Reliability, Validity